Hubungan Pengetahuan Dagusibu dengan Penggunaan Antibiotik pada Masyarakat di Kecamatan Denpasar Utara - Kadek Mirah Triyade Suwena; Putu Eka Arimbawa; I Gusti Agung Haryawan; I Gusti Ayu Rai Widowati (Lembaga Kajian Ilmu Pengetahuan dan Publikasi Indonesia, 2025)
Society does not yet have proper behavior regarding the use of antibiotics, this results in antimicrobial resistance. Antimicrobial resistance is a threat to the world, causing more deaths than cancer. Knowing the relationship between DAGUSIBU knowledge and the use of antibiotics in the community in North Denpasar District. This research is a quantitative observational study with a cross sectional design. recruited purposively. The instruments used have been tested for validity and reliability. Data were analyzed by Rank Spearman using SPSS version 26.0.A total of 400 respondents participated (response rate = 80.0%). Knowledge level is high (n=; 64%). The use of antibiotics is classified as appropriate 52.3%. The results of the Rank Spearman correlation test show the value of the correlation coefficient = 0.582; p = 0.001, meaning that there is a significant relationship with a fairly strong correlation coefficient. To increase public knowledge regarding the use of antibiotics, it is hoped that pharmacy staff can provide DAGUSIBU education on antibiotics.